2012
DOI: 10.1097/iop.0b013e31825e697c
|View full text |Cite
|
Sign up to set email alerts
|

Subciliary Incision for External Dacryocystorhinostomy

Abstract: Subciliary DCR provides an excellent functional cosmetic scar outcome while retaining the access and advantages of external DCR procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Using a similar approach with the incision placed in a relaxed skin tension line of the eyelid, Akaishi et al 30 reported that patients graded their scar on average between invisible and minimally visible at 6 months after surgery. Dave et al 21 studied the subciliary approach in 16 patients. At the final follow up, 88% of patients rated the scar as invisible and 100% rated it as invisible or minimally visible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a similar approach with the incision placed in a relaxed skin tension line of the eyelid, Akaishi et al 30 reported that patients graded their scar on average between invisible and minimally visible at 6 months after surgery. Dave et al 21 studied the subciliary approach in 16 patients. At the final follow up, 88% of patients rated the scar as invisible and 100% rated it as invisible or minimally visible.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] However, several studies have proved that a wellplaced exDCR incision can result in an inconspicuous scar to surgeon and patient alike. [17][18][19] Previously described incision sites include relaxed tension lines of the lower eyelid, 20 and subciliary 21 and transconjunctival incisions. 22 Although mentioned in the literature, incision in the tear trough has not been studied prospectively.…”
mentioning
confidence: 99%
“…Nonetheless, a number of external DCR scar assessment studies only had subjective patient grading but without physician grading [3,10,30,31]. For those studies that included physician grading, they relied on a non-validated categorical grading scale based solely on whether the scar is invisible to very visible [8,9,[11][12][13]21]. This simple grading scale neglected other parameters of scar assessment such as size, pigmentation, and suture marks.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the surgical success, patients were asked to evaluate each of their incisions (using a mirror) by using the following scar grading scale described previously: 0 invisible, 1 minimally visible, 2 moderately visible, 3 very visible [8,9,21]. In addition, patients indicated their aesthetic satisfaction of the skin incisions by placing a single mark on a standard 100 mm visual analogue scale (VAS) [22].…”
Section: Aesthetic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation